REPRESENTASI ALIENASI CODA PADA TOKOH BORI DALAM FILM KOREA BORI - Ulandari, Dea Monica; Burhan, Ph.D, Amelia (UI Scholars Hub, 2025)
CODA or Children of Deaf Adults are the descendants of deaf parents who have the ability to hear and speak. They also have their own emotional stress because they have to adapt to two worlds, the hearing and deaf worlds. This leads to feelings of alienation which are also reinforced by external and internal factors. This research aims to find out how influential the feeling of alienation is on Bori's identity as a CODA in the Korean movie Bori. The character Bori is a CODA and the only person with hearing ability in her deaf family. The method used in this research is descriptive qualitative with a mimetic approach and alienation theory by Seeman Melvin (1959). The results show that the alienation felt by the character Bori comes from the different ways of communicating with her family and the expectations that are indirectly imposed on her and the social environment factors that do not validate her feelings of alienation as a CODA. With internal and external emotional encouragement, Bori can overcome her feelings of alienation and find her true identity.